2017
DOI: 10.2217/fvl-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years of HIV in Pakistan: A Systematic Review of Prevalence and Current Scenario

Abstract: Aim: HIV infection was first reported in Pakistan in 1987. Since then it has been a point of concern in the country. Materials & methods: We searched the literature on HIV in Pakistan using different keywords in Google, Pubmed, PakMediNet and GoogleScholar, and found a total of 64 articles dating from 1987 to 2016. Results: Total 4,882,450 individuals from Pakistan have been screened for HIV since last 30 years. The estimated overall prevalence was 0.041% (95% CI: 0.0–6.79). The highest infection rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Although Pakistan is a low HIV prevalence country, however, the IDUs are playing a vital role in HIV transmission (Strathdee et al, 2010). Since the first HIV epidemic among PWIDs in Larkana (Shah et al, 2004), HIV-1 has now become well established in PWIDs across the country and despite of various precautionary efforts, the epidemics have relatively expanded among PWIDs with the passage of time (Ali et al, 2017). A strong association was also observed in PWID involved in sexual activities because after sharing needles the major route of HIV transmission is sexual transmission for possible spread of disease among population of large geography (Ball et al, 2019;Conrad et al, 2015;Stone et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although Pakistan is a low HIV prevalence country, however, the IDUs are playing a vital role in HIV transmission (Strathdee et al, 2010). Since the first HIV epidemic among PWIDs in Larkana (Shah et al, 2004), HIV-1 has now become well established in PWIDs across the country and despite of various precautionary efforts, the epidemics have relatively expanded among PWIDs with the passage of time (Ali et al, 2017). A strong association was also observed in PWID involved in sexual activities because after sharing needles the major route of HIV transmission is sexual transmission for possible spread of disease among population of large geography (Ball et al, 2019;Conrad et al, 2015;Stone et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence rate was estimated at 0.041% (95% CI: 0.0-6.79). Maximum infection rate 15.05% (SE=4.27%) were observed among injecting drug users, followed by refugees 2.63%, sex Workers 2.63% and Prisoners 1.32% (Ali et al, 2017). According to UNAIDS estimates, about 130,000 people are living with HIV in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of knowledge and poor prevention attitudes including the use of condoms were recognised as major risks for increasing burden of the disease. A recent systematic review also identified migrants, prisoners and multi-transfused patients with high prevalence of HIV [ 4 ].…”
Section: Introductionmentioning
confidence: 99%